Werckmeister harmóniák - Tarr, Béla (Hungary : Mokép, 2000)
The story takes place in a small town in the Hungarian Great Plain in an extremely cold winter. Several hundreds of people are gathering on the main square around a circus tent to see the stuffed body of a whale. This attraction disturbs the town’s life – far from peaceful anyway. Tensions escalate to an unbearable level with the appearance of the Prince, triggering off murderous impulses. Horrible events reach a similarly horrible end.
Duration: 02:25:00
Keywords: Fiction films